Efektivitas Model Pembelajaran SAVI dalam Mata Pelajaran IPA di Kelas V Sekolah Dasar - Siti Nur Afifah; Septi Budi Sartika (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
This study aims to describe the effectiveness of the SAVI learning model in science subjects in grade 5 of SD. Data collection techniques using observation, tests, and questionnaires. The results showed that: (1) The teacher's ability to manage science learning using the SAVI learning model was categorized in good classification. With a percentage of 100% at the second meeting and third and 90% at the first meeting. (2) Student activity in science learning with the SAVI learning model, which is in very good classification with a percentage of 100%. (3) the academic response is classified as very good with an average score of 90%. (4) the results of student observations in science learning after the SAVI model was applied to grade 5 students of SD were categorized in very good and effective classification. Based on the calculation of N-gain with a value of 71.3659 included in the high category which is in the interval 0.7≥g <1. Based on the results of the study, it can be concluded that the effectiveness of the SAVI learning model in science learning for grade 5 SD can be said to be effective.